Less is more: once vs. multiple radioactive iodine (RAI) therapy in patients with RAI-avid pulmonary micrometastatic differentiated thyroid cancer. - Shi, Cong; Sun, Di; Sun, Yu-Qing; Zhang, Xin; Liu, Sheng-Yan; Li, Qi-Jun; Pan, Yi-Jin; Guo, Wen-Ting; Zhang, Ying-Qiang; Jin, Xiao-Na; Liu, Yu; Lin, Yan-Song (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: To date, the survival benefits of multiple radioactive iodine therapies (RAIT) in RAI-avid pulmonary micrometastatic differentiated thyroid cancer (DTC) remain debatable. This study aimed to compare the progression-free survival (PFS) benefits between those received only once RAIT (o-RAIT) and multiple RAITs (m-RAIT) in such patients. Methods: Patients with RAI-avid pulmonary micrometastatic DTC were included and divided into either o-RAIT or m-RAIT group according to the number of RAIT cycles. The response to first RAIT in all patients and last RAIT in m-RAIT were evaluated and classified as partial response (PR), stable disease (SD), and progressive disease (PD). PFS was defined as the time from first RAIT to PD. Logistic regression analysis and Kaplan–Meier survival curves were employed to identify risk factors and estimate PFS, with propensity score matching (PSM) to reduce confounders. Results: A total of 117 patients with RAI-avid pulmonary micrometastatic DTC were retrospectively included, with 38 (32.5%) from o-RAIT and 79 (67.5%) from m-RAIT. Patients from m-RAIT exhibited younger age at diagnosis, more local persistent disease before RAIT, and more metachronous metastasis compared with o-RAIT group (all P < 0.05). In the comparison of RAIT response, there was no difference in the first RAIT response between the o-RAIT and m-RAIT, while the last RAIT response of m-RAIT is worse not only than o-RAIT (P = 0.005), but also than their own first RAIT response (P = 0.0003). Multivariate analysis revealed age at diagnosis (over 45 years old) (P = 0.006) and local persistent disease before RAIT (P = 0.001) were independent risk factors for PD after RAIT, while number of RAIT cycles was not. To minimize potential confounders, the risk factors for PD and follow-up time were matched by PSM, after which, no significant difference in PFS was observed between the matched o-RAIT and m-RAIT (5-year PFS rate: 83.6% vs. 81.6%, P = 0.808). Conclusions: In patients with RAI-avid pulmonary micrometastatic DTC, o-RAIT exhibited non-inferior PFS benefits compared with m-RAIT, suggesting the "less is more" management strategy of RAIT towards such patients.